2015
DOI: 10.1016/j.petrol.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of non-planar hydraulic fracture propagation in brittle and ductile rocks using XFEM with cohesive zone method

Abstract: Cite this article as: HanYi Wang, Numerical modeling of non-planar hydraulic fracture propagation in permeable medium using XFEM with cohesive zone m e t h o d , Journal of Petroleum Science and Engineering, http://dx. AbstractWith the increasing wide use of hydraulic fracturing in the petroleum industry, it is essential to accurately predict the behavior of fracture propagations based on the understanding of fundamental mechanisms governing the process. For unconventional resources exploration and development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
92
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(95 citation statements)
references
References 43 publications
3
92
0
Order By: Relevance
“…As shown in Figure 1, some weak points often exist around the wellbore during construction of the PFC 2D model, where may be locations of fracture initiation dependent on parameter combination applied in different cases (Table 1). Because the initial onset of fracture is influenced by wellbore geometry, local stress concentration and rock strength, if the fracture initiation is misaligned with the direction of PFP, the fracture will reorient itself to propagate in the direction of least resistance (Wang, 2015). As shown in Figures 2 and 3, fracture propagation will align or gradually reorient to the direction of maximum horizontal in-situ stress in all cases of in-situ stress ratio larger than 1.0.…”
Section: The Influence Of In-situ Stress Ratiomentioning
confidence: 95%
See 3 more Smart Citations
“…As shown in Figure 1, some weak points often exist around the wellbore during construction of the PFC 2D model, where may be locations of fracture initiation dependent on parameter combination applied in different cases (Table 1). Because the initial onset of fracture is influenced by wellbore geometry, local stress concentration and rock strength, if the fracture initiation is misaligned with the direction of PFP, the fracture will reorient itself to propagate in the direction of least resistance (Wang, 2015). As shown in Figures 2 and 3, fracture propagation will align or gradually reorient to the direction of maximum horizontal in-situ stress in all cases of in-situ stress ratio larger than 1.0.…”
Section: The Influence Of In-situ Stress Ratiomentioning
confidence: 95%
“…With increasing fluid pressure in the domains, the aperture can reach to 1.03 × 10 -6 m when the bonding stress condition between particles is tensile. Many researches demonstrated that hydraulic fractures initiate and propagate along a preferred fracturing plane or path (PFP), which is the direction of least resistance and generally along maximum in-situ stress (Wang, 2015). As shown in Figure 1, some weak points often exist around the wellbore during construction of the PFC 2D model, where may be locations of fracture initiation dependent on parameter combination applied in different cases (Table 1).…”
Section: The Influence Of In-situ Stress Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…Chen (2012) used the commercial finite element code, ABAQUS, where the stress intensity model is replaced by a cohesive-zone fracture tip model, to simulate fracture propagation driven by fluid, and their modelling results are in good agreement with the 2D PKN and KGD solutions. Wang (2015) also used an ABAQUS embedded extended finite element method and cohesive zone method to model fracture initiation and propagation in different brittle rocks, and the results show that fluid pressure field and fracture geometry are significantly affected by the rock in-elastic deformations.…”
Section: Introductionmentioning
confidence: 99%